Efectos de la Vitamina E más Prebiótico (Arabino galactosa) en agua de bebida en el impacto post vacunal en las fases de desarrollo de pollos BB, Cantón Babahoyo. - Egda Paredes Macias., Egda (2016)
SUMMARY. This investigation was carried out for six weeks (42 days) in the city of Babahoyo, at the Experimental Farm St. Paul of the Faculty of Agricultural Sciences (FACIAG) School of Veterinary Medicine at the Technical University of Babahoyo, is located at km 7.5 of the road Babahoyo Montalvo Province Rivers to a height of 7 meters whose geographical location is 01 ° 47'49 "S latitude and longitude 79 ° 32'00" W and average annual precipitation 1987.04 mm. It has a temperature of 25 ° C. The aim of the research was to evaluate the effect of vitamin E plus prebiotic on the post-vaccination impact on the development phases of chicks BB, the trial lasted 42 days (6 weeks), applying the product Vitec (vitamin E more prebiotic (arabino galactose), before, during and after application of the vaccine (Newcastle Bronchitis more). BB 180 chicks from Cobb 500 line, the design used was completely random (D.C.A.) with three treatments and six replications (10 chicks per replicate) forming 18 experimental units were used. (EU). The results between witness and treatment showed no statistical significance between treatments, however at the end of trial (week 6) treatment 1 has the highest feed intake in relation to the weights, the comparison between means in relation to witnesses, determined that the 20cc and 50cc treatments with vitamin E plus prebiotic (galactose arabino), had higher weight at the end of the trial being both higher than the control. On a cumulative feed conversion, there is no statistical significance for any of the treatments. As for size of villi in the small intestine of birds at 21 days of the trial it was observed that once practiced the corresponding observations in sample 1 is no statistical significance between the three treatments being superior treatment 1, the second shows the treatment T0 and T1 are not statistically different but both differ from the first treatment T2 being higher for sample 3 there were no significant differences between the treatments and finally on average no significant difference between the three treatments being superior in T1. The economic analysis of the trial treatments determines that the T1 (20 ml / bird) the highest net profit treatment followed by treatment T2 being both higher than the control was obtained. According to the analysis of dominance of the trial treatments T2 is determined that the treatment has dominance because their variable costs and net profit is less, not treatment T1 has the highest net profit followed by treatment T0. The marginal analysis of treatments nondominated trial a marginal rate of return of 120% was obtained being this an acceptable technology because it exceeds the minimum acceptable rate of return (100%) this means that for every dollar of investment is recovered $ 1.28.